Adenosinergic axis and immune checkpoint combination therapy in tumor: A new perspective for immunotherapy strategy - Liu, Zhaoyun; Liu, Xiaohan; Shen, Hongli; Xu, Xintong; Zhao, Xianghong; Fu, Rong (Frontiers in Immunology, 2022)
Tumor cells escape anti-tumor immune response in various ways, including functionally shaping the microenvironment through secretion of various chemokines, cytokines, etc. Adenosine is a powerful immunosuppressive metabolite, which is frequently found to be elevated in the extracellular tumor microenvironment (TME). Thus, it has been proposed as a novel antitumor immunoassay to target adenosine generating enzymes such as CD39, CD73, and adenosine receptors in recent years. The discovery of the immune checkpoint such as programmed cell death 1(PD-1) and cytotoxic T lymphocyte antigen 4 (CTLA-4), have also greatly changed the treatment methods and ideas of malignant tumors. The idea of malignant tumor immunotherapy has been developed from point-to-point therapy targeting immune checkpoint to combine different points of different pathway to create a kind of therapy based on macroscopic immune regulatory system network. This article reviews the theoretical basis of adenosine energy axis and immune checkpoint combined therapy for malignant tumors and the latest advances in malignant tumors.